1995
DOI: 10.2527/1995.73123743x
|View full text |Cite
|
Sign up to set email alerts
|

Fate of the dominant follicle, embryonal survival, and pregnancy rates in dairy cattle treated with prostaglandin F2 alpha and progestins in the absence or presence of a functional corpus luteum.

Abstract: Our objective was to examine the role of progestin type on serum concentrations of progesterone (p4) and estradiol-17 beta (E2), ovarian follicular dynamics, and fertility in cattle in the presence or absence of a corpus luteum (CL) in an estrus synchronization scheme using progestin and PGF2 alpha. In Exp. 1, 325 cows and heifers were given one injection of PGF2 alpha (d 0) and then assigned randomly within parity to five treatments: to receive a second PGF2 alpha injection 14 d later (control); to receive no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
25
1
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(33 citation statements)
references
References 29 publications
4
25
1
3
Order By: Relevance
“…In the present study, however, pregnancy losses in both groups were 18.9%, which are in agreement with the results of previous studies (Smith and Stevenson, 1995;Fricke et al, 1998;Rivera et al, 2004) which reported that 5% to 20.5% of pregnancies in lactating dairy heifers were lost between 30 and 75 days of gestation. In addition, the proportion of Holstein heifers which experienced pregnancy loss between 40 and 90 days of gestation was 3.4% (Chebel et al, 2007).…”
supporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, however, pregnancy losses in both groups were 18.9%, which are in agreement with the results of previous studies (Smith and Stevenson, 1995;Fricke et al, 1998;Rivera et al, 2004) which reported that 5% to 20.5% of pregnancies in lactating dairy heifers were lost between 30 and 75 days of gestation. In addition, the proportion of Holstein heifers which experienced pregnancy loss between 40 and 90 days of gestation was 3.4% (Chebel et al, 2007).…”
supporting
confidence: 93%
“…Early embryonic mortality in cows returning to oestrus before day 24 after insemination is around 20.5% to 43.6%, and late embryonic mortality in cows returning to oestrus after day 24 is around 8.0% to 17.5% (Humblot, 2001). However, 5% to 20.5% of pregnancies in lactating dairy heifers were lost between 30 and 75 days of gestation (Smith and Stevenson, 1995;Fricke et al, 1998;Rivera et al, 2004). The hypotheses of the current study was that incorporating the intravaginal progesterone device between day 14 and day 20 after TAI synchronise the return to oestrus and increase the reinsemination rate of non-pregnant heifers.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to our findings, a previous report showed higher conception rate in heifers (67.9%) than cows (53.1%) [52]. The present study recorded lower pregnancy loss (5.1%) in cows compared with previous reports where the loss in cows was 20% when PGF2α/ progestins was used [53]. Infectious diseases, and non-infectious factors such as poor management systems, milk yield, parity, BCS, ambient temperature [54] can cause pregnancy loss.…”
Section: Discussioncontrasting
confidence: 56%
“…The recorded fertility variables in the current study using the CIDRsynch protocol were greater than those reported with the SE and Ovsynch protocol. Combined fertility with use of the CIDRsynch protocol might be attributed to the concept that, under progesterone dominance, the dominant follicle either grows, regresses with a subsequent initiation of another wave of follicular development, or there is ovulation from the dominant follicle and a new follicular wave emerges (Smith and Stevenson, 1995). Insertion of CIDR elevated the serum progesterone concentration to 1-2 ng/ml to 15 days posttreatment (Uehlinger et al, 1995).…”
Section: Discussionmentioning
confidence: 96%